Leprosy in adults in the metropolitan region of Belém: analysis of the classification of the degree of physical and operational disability - Costa, Tanise Nazaré Maia; Pereira, Cybelle Cristina; de Freitas, Elaine Vilhena; Neto , Guilherme Imbiriba Lisboa; Viana , Isabela Martins; de Souza, Laura Correa; Cordeiro , Neylane Araújo; Mendes, Yasmin Batista (Seven Editora, 2023)
The current study aimed to analyze clinical data on the classification of the degree of physical and operational disability of the disease in the state of Pará, specifically the Metropolitan Region of Belém (RMB) among adults aged 20-50 years in the period from 2016 to 2020 to obtain information about the disease. The aim of this study was to understand their behavior and provide updated data to healthcare professionals. It has a descriptive, indirect, observational and retrospective character through data obtained from the Ministry of Health website. Leprosy is a public health problem in Brazil, it stands out almost exclusively in developing countries. There was a higher prevalence of diagnoses of grade 0 classification and multibacillary operational classification of the disease in the four years studied and in all municipalities. Through this research, we sought to collect information about the infection in question, in order to inform how the numbers of this pathology have an impact on the quality of life in the State of Pará and the importance of combating it for the improvement of the health conditions of the local population. DOI: https://doi.org/10.56238/colleinternhealthscienv1-128